Prudence and prevention – empirical evidence - Mayrhofer, Thomas; Schmitz, Hendrik (Economics letters, 2025)
•We provide the first representative evidence on the link between prudence and preventive behavior.•Prudent individuals above 60 or with chronic illness are less likely to receive influenza vaccination.•No significant association is found for younger and healthy individuals with low baseline vaccination rates.•Results highlight the role of higher-order risk preferences in shaping real-world self-protection decisions. Theory shows that optimal prevention decisions in the sense of self-protection (i. e., primary prevention) depend not only on the level of (second-order) risk aversion but also on prudence (third-order risk aversion). We use a unique dataset that combines data on higher-order risk preferences and observed real-world preventive behavior and provide the first representative evidence of a negative relationship between prudence and self-protection: We find that prudent individuals in the high-risk group (above the age of 60 or chronically ill) indeed invest less in self-protection as measured by influenza vaccination. This does not hold for younger and healthy individuals for whom influenza vaccination rates are low in general.